Essays on Japanese economy - Tsuru, Shigeto (Tokyo, 1958)
When one resides abroad, as long as I have done. one is frequently called upon to explain or discuss about one's country. My interest in various aspects of the Japanese economy thus developed as more of an avocation, with intermittent concentration as the occasion demanded. All the essays included here, except one, were originally written with western readers in mind, each against the background of specific time and problem. The exception is the essay on "Economic fluctuations in Japan, 1868-1893," which is purely academic in character. Since all of them were published once before, I have indicated, at the very beginning of each essay, the year when it was written and the name of the publication where it first appeared, along with a few explanatory notes. I am grateful for the permissions given to me for reproduction by the publications concerned.
Keywords: Japan - Economic conditions